Factors Influencing Chinese Students’ Decisions to Study in the United States - Austin, Larry; Shen, Libi (Journal of International Students, 2016)
The central research question was: Why do Chinese students want to study in the United States? The participants were 20 Chinese students who studied in the U.S. Ten interview questions were used and data were processed in NVivo 10. Five major themes emerged from this study: (a) American culture benefits foreign perceptions of education in the U.S.; (b) increased personal wealth increases demands for educational freedom; (c) Chinese test performance does not indicate education quality; (d) Chinese culture clashes with students’ desire for self-actualization; and (e) an education in the U.S. is considered an immigration stepping stone.